Editorial: Bacteriophages and their lytic enzymes as alternative antibacterial therapies in the age of antibiotic resistance - São-José, Carlos (2022)
Editorial on the Research Topic Bacteriophages and Their Lytic Enzymes as Alternative Antibacterial Therapies in the Age of Antibiotic Resistance